La obligación de negociar en el derecho internacional: un análisis a la luz de la clasificación de las obligaciones de comportamiento y de resultado - Moreno, Antonino (2019)
This work examines the obligation to negotiate regarding the case filed by Bolivia before the International Court of Justice concerning the obligation to negotiate sovereign access to the Pacific Ocean. For that purpose, it will put emphasis on the strategy followed by Bolivia, regarding certain pros and cons of its case theory. After that, it will study the obligation to negotiate and its development in the international jurisprudence. Subsequently, emphasiswill be done to the theoretical distinction between the obligations of means and obligations of result with the aim to identify in which of these two categories does the obligation to negotiate fit. Finally, it concludes supporting that the obligation to negotiate could be qualified as an obligation of conduct or an obligation of result, according to the content that it has.